2008
DOI: 10.1017/s1355617708080934
|View full text |Cite
|
Sign up to set email alerts
|

Relation of individual differences in impulsivity to nonclinical emotional decision making

Abstract: Impulsivity has been identified as a behavioral precursor to addiction, and may be the manifestation of a neurological vulnerability. The present study investigated whether individual differences in impulsivity were associated with performance on the Iowa Gambling Task (IGT, a test of emotional decision making thought to be associated in part with ventromedial prefrontal cortex function) and the Wisconsin Card Sorting Task (WCST, a set-shifting thought to be associated in part with dorsolateral prefrontal cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
3
38
4
1
Order By: Relevance
“…However, the main effect of CES-D depression scores and EBR from the second step were not significant in the last step of the regression, p >.10. Because some research has shown that individual difference effects only emerge in the last block of IGT trials after learning is complete (Sweitzer, Allen, & Kaut, 2008), we also conducted regression analyses within each of the five 20-trial blocks. Results revealed that this interaction between depressive symptoms and EBR on IGT performance was significant in blocks 2 (ÎČ=.77, p =.003) and 3 (ÎČ=.55, p =.04).…”
Section: Resultsmentioning
confidence: 99%
“…However, the main effect of CES-D depression scores and EBR from the second step were not significant in the last step of the regression, p >.10. Because some research has shown that individual difference effects only emerge in the last block of IGT trials after learning is complete (Sweitzer, Allen, & Kaut, 2008), we also conducted regression analyses within each of the five 20-trial blocks. Results revealed that this interaction between depressive symptoms and EBR on IGT performance was significant in blocks 2 (ÎČ=.77, p =.003) and 3 (ÎČ=.55, p =.04).…”
Section: Resultsmentioning
confidence: 99%
“…Highly impulsive groups show the greatest impairment in performance during the latter trials of the IGT (Sweitzer et al, 2008). Accordingly, the net IGT was calculated by subtracting the number of cards selected from disadvantageous decks from the number of cards selected from advantageous decks over the last two blocks: [(C+D) -(A+B)].…”
Section: Measures Of Impulsivity In Aspd Iowa Gambling Taskmentioning
confidence: 99%
“…Altered decision making is frequently associated with cognitive impulsivity [1,4,5]. It is the product of an imbalance between two separate, but interacting, neural systems: (1) an impulsive, amygdala-dependent system, which controls immediate and "somatic" behaviour related to a decision and (2) a reflective, prefrontal-dependent system [6], which evaluates the future prospects related to the decision [4].…”
Section: Cognitive Impulsivitymentioning
confidence: 99%